Type 2 Diabetes Mellitus Facilitates Shift of Adipose-Derived Stem Cells Ex Vivo Differentiation toward Osteogenesis among Patients with Obesity - Margarita Agareva; Iurii Stafeev; Svetlana Michurina; Igor Sklyanik; Ekaterina Shestakova; Elizaveta Ratner; Xiang Hu; Mikhail Menshikov; Marina Shestakova; Yelena Parfyonova (Life, 2022)
Objective: Sedentary behavior with overnutrition provokes the development of obesity, insulin resistance, and type 2 diabetes mellitus (T2DM). The main progenitor cells of adipose tissue are adipose-derived stem cells (ADSCs) which can change differentiation, metabolic, and secretory phenotypes under obesity conditions. The purpose of this study was to evaluate ADSC osteogenesis activity among patients with obesity in normal glucose tolerance (NGT) and T2DM conditions. Methods: In the study, ADSCs from donors with obesity were used. After clinical characterization, all patients underwent bariatric surgery and ADSCs were isolated from subcutaneous fat biopsies. ADSCs were subjected to osteogenic differentiation, stained with Alizarin Red S, and harvested for real-time PCR and Western blotting. Cell senescence was evaluated with a β-galactosidase-activity-based assay. Results: Our results demonstrated the significantly increased calcification of ADSC on day 28 of osteogenesis in the T2DM group. These data were confirmed by the statistically significant enhancement of RUNX2 gene expression, which is a master regulator of osteogenesis. Protein expression analysis showed the increased expression of syndecan 1 and collagen I before and during osteogenesis, respectively. Moreover, T2DM ADSCs demonstrated an increased level of cellular senescence. Conclusion: We suggest that T2DM-associated cellular senescence can cause ADSC differentiation to shift toward osteogenesis, the impaired formation of new fat depots in adipose tissue, and the development of insulin resistance. The balance between ADSC adipo- and osteogenesis commitment is crucial for the determination of the metabolic fate of patients and their adipose tissue.